Involuntary Simplicity: Changing Dysfunctional Habits of Consumption. (1st February 1994) - Claxton, Guy
Abstract : Why is it so difficult for 'voluntary simplicity' to become truly voluntary? It is suggested that an important distinction has to be made between beliefs which are 'espoused' and those which are 'embodied'. Certain crucial systems of embodied beliefs constitute traps, in the sense that they set, invisibly, a person's motivational agenda, and bias perception against their own detection. This analysis makes it clear why certain popular forms of campaigning and education are ineffective; and suggests that some methodologies of self-transformation associated with spiritual traditions such as Buddhism may have much to offer the environmental movement.